(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The article provides some feedback on the use of didactic requirements and new pedagogical technologies in the organization of mathematics lessons in secondary schools. The didactic reuirements in learning classes are described. The results that can be achieved through the use of new pedagogical technologies are listed.